2011
DOI: 10.1111/j.1756-185x.2011.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold capillaroscopy by digital microscope in an Indian population with systemic sclerosis

Abstract: Nailfold capillaroscopy changes in SSc are related to disease subset and MRSS. NFC with digital microscope is a simplified, inexpensive, outpatient procedure with results comparable to previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…However, our multivariate analysis retained only absence of sclerosis and telangiectasia as being significantly associated with normal/nonspecific NVC. These results are consistent with those previously reported that showed NVC severity to be associated with cutaneous sclerosis extent and significantly associated with SSc subsets [6,19,30]. Indeed, although early and active abnormal NVC patterns have more frequently been described for lcSSc and the late NVC pattern for dcSSc and during active disease [5,6,29], the normal NVC pattern seems to be more frequent in lcSSc than dcSSc [18,19,20].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, our multivariate analysis retained only absence of sclerosis and telangiectasia as being significantly associated with normal/nonspecific NVC. These results are consistent with those previously reported that showed NVC severity to be associated with cutaneous sclerosis extent and significantly associated with SSc subsets [6,19,30]. Indeed, although early and active abnormal NVC patterns have more frequently been described for lcSSc and the late NVC pattern for dcSSc and during active disease [5,6,29], the normal NVC pattern seems to be more frequent in lcSSc than dcSSc [18,19,20].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the SSc-specific NVC pattern is accepted as an independent factor predictive of RP progression to SSc, with a higher odds ratio than for other connective tissue diseases [14,16]. At the same time, the percentages of SSc patients having normal/nonspecific NVC patterns varied between 4 and 20%, depending on patient recruitment [7,17,18,19]. In most of studies using the LeRoy and Medsger criteria, a normal NVC pattern was more common in patients with lcSSc than dcSSc and was observed in up to 38% of lcSSc patients [18,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sato et al [13] and Bhakuni et al [14] found that capillary loss was associated with higher skin scores as assessed by modified Rodnan skin scores. Also the significant loss of capillaries in diffuse cutaneous disease as compared to limited disease was observed by Bhakuni et al [14] and Ostojic et al [15] in their study. These studies showed, with the increasing skin thickness, the capillary density decreases and thus patients with diffuse cutaneous disease which has higher skin scores have more marked capillary loss.…”
Section: Nailfold Capillaroscopy and Correlation With Organ Involvementmentioning
confidence: 99%
“…Architectural pattern: 6 descriptive classes: cuticilis, open, tortuous, crossed, bushy, and bizarre will be noted. Intra- and inter-observer variability/reliability of < 10% will be acceptable [ 27 ]. Echocardiography Assessment Equipment & Method …”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%